Ножі з клеймами Литовської доби з Київщини - Романюк, В.В. (Археологія, 2011)
Публікуються кілька ножів Литовської доби, знайдені в Таращанському районі Київської області. В 2009 г. в Таращанском рне
Киевской обл. были случайно найдены несколько образцов ножей с клеймами
западноевропейского производства. Типологическое их сравнение с клеймами, найденными в русских городах,
позволило установить их принадлежность к одному из интересных и мало изученных на юге Киевщины периодов
Великого княжества Литовского. Several samples of knives with stamps of Lithuanian period of Western European production were accidentally discovered
in Tarascha district in Kyiv region in 2009. They were compared typologically with a collection of stamps, discovered in
excavations of Rus Cities and identified by their chronological affiliation to one of the interesting and littlestudied
periods
of Grand Duchy of Lithuania in the south of Kyiv region.